ASSESSMENT OF FECUNDITY AND GONADO-SOMATIC INDEX OF POND REARED CIRRHINUS MRIGALA (HAM., 1822) - DAS, S. C. S.; PATHAK, R. K.; KHAN, A.; JOSHI, K. D. (Journal of the Inland Fisheries Society of India, 2021)
Mean body weight for both the sexes was 1270.9Â±10.96 g with mean total length of 473.95Â±11.92 g. GSI (%) values ranged from 0.23 to 7.93 in male with peak value in July (7.93) and 0.83 to 16.9 in female with peak value in July (16.09).The gonads attained maximum weight of 472.5 and 124.41g for females and males, respectively in the month of July and minimum in November. The fish has only one spawning season extended from May to August as indicated by the peaks of GSI with peak season between July-August. The relative and absolute fecundity varied from 69,244 to 2, 15,680/ kg and 74,783 to 4, 14, 416, respectively. Fecundity showed a significant positive correlation with total length (0.749), gonad weight (0.747) and body weight (0.807) of the sampled fish. C. mrigala exhibited maximum reproductive potential and fecundity in the month of July compared to June and August in the eco-climatic conditions of Eastern Uttar Pradesh. Key words: Gonado-somatic index, fecundity, Cirrhinus mrigala, Eastern Uttar Pradesh